1988
DOI: 10.1104/pp.87.1.244
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Bound Ribulose Bisphosphate Correlates with Deactivation of Ribulose Bisphosphate Carboxylase in Leaves

Abstract: Previous reports indicate that ribulose 1,5-bisphosphate (RuBP) binds very tightly to inactive ribulose bisphosphate carboxylase (rubisco)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 10 publications
(16 reference statements)
7
58
0
Order By: Relevance
“…In separate experiments, RuBP levels in the wild-type plants were also measured. In agreement with previous reports examining Arabidopsis (11) and other species (reviewed in ref. 28), the level of RuBP was initially in excess of the level of Rubisco-binding sites under high light.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In separate experiments, RuBP levels in the wild-type plants were also measured. In agreement with previous reports examining Arabidopsis (11) and other species (reviewed in ref. 28), the level of RuBP was initially in excess of the level of Rubisco-binding sites under high light.…”
Section: Resultssupporting
confidence: 82%
“…Previous experiments on the wild-type plants have shown that the activation state of Rubisco under normal atmospheric conditions varies with light intensity, ranging from about 40% maximal at very low light to nearly 100% at high light (11). In sharp contrast, the activation state in the rca plants decreases on illumination with either high or low light intensities (27).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…6, 8, and 12), and results from the high affinity of RuBP for the decarbamylated catalytic site (kD = 20 nM) (8). More recently, it has been demonstrated that RuBP can be bound in a noncatalytic fashion to Rubisco in leaves which were exposed to conditions that caused deactivation of the enzyme (3,5,10,23). This bound RuBP is presumably removed by another light-dependent enzyme, Rubisco activase (17).…”
Section: Rubp Levelsmentioning
confidence: 99%
“…After the samples were thawed and centrifuged, the supernatant was neutralized with KOH. RuBP was determined by incorporation of 14C0, into P-glycerate in an assay mixture consisting of 100 mM Tricine (pH 8.1), 10 mM MgCI,, 10 mM NaH14C0,, and 5 pg of activated Rubisco (Brooks and Portis, 1988).…”
Section: Enzyme and Metabolite Assaysmentioning
confidence: 99%